Inovasi Strategi Pembelajaran : Membentuk Mahasiswa Menjadi Pendidik Andal di Era Digital - Muhaiminah Darajat (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This research aims to explore and analyze learning strategy innovations in shaping students as reliable educator candidates who are able to face educational challenges in the digital era. The main focus of the research is the application of technology-based learning approaches, collaboration, and creative strategies that place students not only as recipients of knowledge, but also as active subjects who construct understanding through learning experiences. This study was carried out in the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) of the Syarifuddin Lumajang Islamic Religious Institute by involving 30 students who took the learning strategy course. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, classroom observations, and documentation. The findings of the study show that the application of flipped classroom is able to increase student learning independence, while project-based learning strategies encourage creativity and problem-solving skills. In addition, the use of interactive technology such as online quiz applications, discussion platforms, and collaborative media strengthens learning motivation while expanding students' digital skills. Although the results showed a positive impact, there were significant obstacles, namely the limitations of technology infrastructure in the campus environment and the low digital literacy of some students. These factors hinder the optimization of innovative learning strategies. Therefore, institutional support is needed in providing technology-based infrastructure, digital literacy training, and continuous mentoring so that students can develop pedagogical competence, professionalism, and adaptive abilities in accordance with the demands of 21st century education. Overall, this study emphasizes that learning strategy innovation supported by technology, collaboration, and support of educational institutions is able to strengthen the process of forming prospective educators who are competent, competitive, and ready to face the dynamics of the world of education in the digital era.